Modeling of 2-DOF Hexapod Leg Using Analytical Method - Agusma Wajiansyah; Supriadi Supriadi; Achmad Fanany Onnilita Gaffar; Arief Bramanto Wicaksono Putra (Universitas Muhammadiyah Yogyakarta, 2021)
Walking robot is one type of mobile platform that has locomotion type